A list of accident scenarios for three legs skewed intersections. (October 2018) - Distefano, Natalia; Leonardi, Salvatore
Abstract: The term 'scenario' is used in the safety field to designate a prototype or a model of an accident process characterised by chains of facts, actions, causal relations and consequences in terms of damage to people and property. The prototypical scenarios, properly realized, provide a basis on which to consider the action to be taken, but also a concrete backup for accident information for use in information campaigns or training. The objective of this study is to define the prototypical accident scenarios for a particular configuration of road intersection: the skewed intersection. Limited sight distance at skewed intersections leads to safety issues. A non-skewed intersection provides the best operating conditions as drivers can easily sense the direction in which they are travelling, estimate the speeds of the opposing traffic and smoothly complete a maneuver in shorter time. In skewed intersections, instead, the ability of drivers to recognize any conflicting vehicles diminishes in comparison to right-angle intersections. The logical-deductive approach used in this paper for the determination of accident scenarios is based on an analysis of a large database of incidents, which occurred on several roads in eastern Sicily on 35 skewed intersections at three-legs. The skew angle of the minor leg of all the intersections studied is between 15° and 20°. This research allowed to develop accident scenarios related to particular configurations of intersections, compatible with the Italian rules. Prototypical scenarios are constructed using samples of accidents occurring on a particular type of study area, especially when they are based on files from in-depth investigations. The method used is an inductive approach, based on an examination of each case, grouping together similar cases and building a prototypical scenario using this case grouping. From the in-depth analysis of database accidents 9 prototypical accident scenarios have been identified for the skewed intersections. Highlights: Accident Scenario is a model of accident process described by actions, causal relations and consequences in terms of damage. Limited sight distance at skewed intersections leads to safety issues. Intersection angle is one of the geometric factors that affects the sight distance available at stop-controlled minor legs. The inductive approach allows research findings to emerge from the typical themes of the raw data, unlike structured methods. List of the Prototypical accident scenarios in three legs skewed intersections.